Life history and reproduction of the neotropical caecilian Siphonops annulatus (Amphibia, Gymnophiona, Siphonopidae), with special emphasis on parental care. (2nd April 2018) - Jared, Carlos; Mailho‐Fontana, Pedro Luiz; Jared, Simone G. S.; Kupfer, Alexander; Delabie, Jacques Hubert Charles; Wilkinson, Mark; Antoniazzi, Marta Maria
Abstract: Due to their mainly fossorial way of life, caecilian amphibians are the least known order of terrestrial vertebrates. Here, we present new observations on the natural history and reproductive biology of the neotropical oviparous, siphonopid caecilian Siphonops annulatus from a long‐term study of this species in the field and in captivity. In the studied population, mating occurs between the end of August and beginning of October, and oviposition between November and December, when rainfall peaks. Egg hatching occurs between the end of December and beginning of January. The complete cycle of maternal care, from oviposition to independent, self‐sufficient offspring lasts about 3 months. After eclosion, the altricial young feed on the mother's specially modified skin (maternal dermatophagy) and are also supplied by a fluid released from coming from the maternal cloaca. Also presented are observations on the burrows, feeding and social behaviour of S. annulatus .